The Influence of Competence and Organizational Commitment on the Performance of Legislative Members with Organizational Culture as an Intervening Variable at the Regional House of Representatives of Kampar Regency - Ray, M. Ravi; Indrastuti, Sri; Mardianty, Desy; Yusnidar, Yusnidar; Amanda, Dea; Yusnita, Riska; Resmi, Fuji Dwi Citra; Marina , Marina (International Journal of Environmental, Sustainability, and Social Science, 2026)
This study aims to describe, analyze, and determine the influence of competence and organizational commitment on the performance of council members, with organizational culture as an intervening variable in the Kampar Regency People's Representative Council (DPRD). This study employed a quantitative statistical research design. Data collection techniques used were observation, questionnaires, and documentation. The sample in this study consisted of 45 council members in Kampar Regency. Partial Least Squares (PLS) analysis was used to analyze the data. The results showed that competence positively influenced council member performance. Organizational commitment positively influenced council member performance. Organizational culture positively influenced council member performance. Competence positively influenced organizational culture. Commitment positively influenced organizational culture. Competence positively influenced council member performance through organizational culture. Commitment positively influenced council member performance through organizational culture. Similarly, with competence, although its influence was positive, the influence of commitment on performance through organizational culture was not statistically significant. It indicates that while commitment is important in improving performance, organizational culture is not always able to significantly bridge this relationship in the context of DPRD members.